Investigating the energy saving potential of thermochromic coatings on building envelopes - Butt, Afaq A.; de Vries, Samuel B.; Loonen, Roel C.G.M.; Hensen, Jan L.M.; Stuiver, Anthonie; van den Ham, Jonathan E.J.; Erich, Bart S.J.F. (Applied energy, 2021)
•Thermochromic (TC) coatings provide heating and cooling savings in buildings.•5 building types and 3 climates were studied.•TC coating properties were optimized according to building types and climates.•Temperature-based control of TC coatings leads to heating penalties in winters. Thermochromic (TC) materials can switch solar absorptance (α) based on temperature stimuli. When coatings with TC properties are applied on building envelope surfaces, the amount of solar heat gains can be controlled to reduce the heating and cooling demand of buildings. To date, limited research has been conducted in investigating optimal TC coating properties for application on opaque building envelopes in various scenarios. In this research, a method to model TC coatings using building performance simulation (BPS) tools has been developed and coupled with python to optimize solar absorption states (α) and switching temperatures and reduce the annual heating and cooling demand. The simulation-based approach has been employed to perform early-stage exploration studies on multiple building types and climates to support material R&D in developing optimized coatings for target applications and assess the potential energy savings. The results indicate that the optimum TC properties are unique to climate and building types. TC coatings with high switching temperatures result in larger energy savings for scenarios with high heating demands, while TC coatings with low switching temperatures produce larger energy savings in scenarios with high cooling demands. Similarly, increasing the high solar absorption (αhigh) to 1 increases the heating savings, while reducing the low solar absorption (αlow) to 0 results in higher cooling savings. Furthermore, it was found that solar irradiance causes temperature spikes triggering the TC coatings to unnecessarily switch from high to low absorptance state in winters leading to heating penalties. Replacing optimal static with TC coatings on terraced houses in the Spanish climate with a 2:3 heating to cooling demand ratio results in 2 to 13% energy savings.